Life cycle, care, and labor informality in Chile, 2017-2022 - Flores-Arenas, Bárbara Alejandra (2025)
This article analyzes labor dynamics with a focus on informal occupations, before, during, and after COVID-19 in Chile. The pandemic exposed the care crisis and how it limited women’s participation in the labor market. Through the estimation of pooled probit models, we delve into the determinants of labor informality and analyze heterogeneities by sex, age brackets, and care responsibilities, delving into the changes that occurred between 2017 and 2022 in the Chilean labor market. The results show that it is younger women and those close to retirement age who are more likely to have an informal occupation and, in all age brackets, this possibility is higher than that estimated for men. In turn, having dependents increases the probability of informal employment more for the former than for the latter, a situation that was aggravated by the pandemic. The conclusions discuss the barriers to accessing and remaining in formal employment: lack of experience and training and caregiving responsibilities. They also underscore the urgency of labor policies that take into account the life cycle of individuals and promote the reconciliation of work, personal, and family life.